2011
DOI: 10.1177/0885066611402165
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in the Coronary Care Unit

Abstract: Symptomatic sustained cardiac arrhythmias are frequently observed in in the coronary care unit and often lead to hemodynamic compromise, especially in the presence of multisystem disease. The predominant arrhythmias noted in intensive care units are tachyarrhythmias, particularly atrial fibrillation and flutter, and ventricular tachycardia. Bradycardias, arguably less life-threatening than tachyarrhythmias, can arise from sinus node dysfunction or atrioventricular conduction block; transient vagally-mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…This fact has also been demonstrated in several studies in which AF was the most common recorded SVT after ACS with an incidence of 8% to 28%. 21 In a prospective study by Goodman et al, 22 which enrolled patients admitted to a general intensive care unit (ICU), new-onset supraventricular arrhythmia was associated with high in-hospital and 1-year mortality. The EuroHeart Failure Survey concerning the management of hospitalized heart failure patients in Europe showed that new-onset AF is an independent predictor of in-hospital mortality and longer ICU and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…This fact has also been demonstrated in several studies in which AF was the most common recorded SVT after ACS with an incidence of 8% to 28%. 21 In a prospective study by Goodman et al, 22 which enrolled patients admitted to a general intensive care unit (ICU), new-onset supraventricular arrhythmia was associated with high in-hospital and 1-year mortality. The EuroHeart Failure Survey concerning the management of hospitalized heart failure patients in Europe showed that new-onset AF is an independent predictor of in-hospital mortality and longer ICU and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac conduction systems play a vital role in the normal rhythm of heart beating. Both inherited diseases (e.g., long QT interval syndrome caused by ion channel abnormity [ 100 ] ) and acquired factors (e.g., coronary heart disease, [ 101 ] viral myocarditis [ 102 ] ) could cause the damage to the cardiac conduction systems, therefore resulting in various types of undesirable arrhythmia. Among them, ventricular tachycardia (VT) is a common yet could be a fatal type without appropriate and timely intervention.…”
Section: Promising Clinical Applications Of Tspci For Ndsmentioning
confidence: 99%
“…Supraventricular tachycardia (SVT) is a generic term for cardiac arrhythmia on an atrial level and comprises atrioventricular nodal reentry tachycardia, atrioventricular reentry tachycardia, ectopic atrial tachycardia, atrial flutter, and atrial fibrillation (Badhwar, Kusumoto, & Goldschlager, 2012; Royster & Melander, 2013). The condition affects approximately 0.2% of the population in the Western world, and the prevalence varies with age, gender, and presence of other diseases (Orejarena et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The SVT can vary from seconds to hours, in some cases days, and they can occur several times a day or less frequently (Walfridsson et al, 2009). Lifestyle factors can cause or trigger SVT, which is why a decreased intake of nicotine, caffeine, and alcohol is recommended (Badhwar et al, 2012; Blomström-Lundquist et al, 2003). Specific self-care, such as bending one’s head down, inhaling deeply, putting cold water on one’s face, or clearing one’s throat, coughing, or straining at an early stage can interrupt the SVT (Smith, Morgans, Taylor, & Cameron, 2012).…”
Section: Introductionmentioning
confidence: 99%